2010
DOI: 10.4103/0301-4738.60090
|View full text |Cite
|
Sign up to set email alerts
|

A case of unusual presentation of Takayasu′s arteritis

Abstract: Takayasu's arteritis is a chronic inflammatory disease of the large and medium-sized arteries. It commonly involves the aorta with its branches and the pulmonary arteries. The retinal hemodynamics suggest that the carotid artery involvement causes diminished retinal blood flow. This is the pathogenetic mechanism of Takayasu's retinopathy with characteristic features of microaneurysms, arterio-venous anastomosis and non-perfused retinal areas. Our case presented as branch retinal artery occlusion with collatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
(12 reference statements)
0
18
0
1
Order By: Relevance
“…The most common clinical features are significantly low blood pressure (BP) and weaker pulses in the upper extremities associated with coldness or numbness of the fingers [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common clinical features are significantly low blood pressure (BP) and weaker pulses in the upper extremities associated with coldness or numbness of the fingers [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…TA has been reported from different parts of the world, but the prevalence is more in oriental countries like Japan, India, Korea and Thailand [3]. The etiopathogenesis of the arthritis is not known, but studies are being conducted regarding the immunological and genetic aspects of the disease [3,4]. In most of the cases, irregular thickening of the walls of the aorta and its branch vessels with intimal stenosis is seen.…”
Section: Introductionmentioning
confidence: 99%
“…Occlusion of the retinal vessels is the other reason for ocular symptoms in TA. It is reported that the retinal vessel involvement is very rare presentation of the disease [4, 6]. Vasa vasorum supports the media and adventitia of the vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The initial inflammation around the vasa vasorum is the main histopathological feature in TA, which causes vascular inflammation and intimal proliferation [4]. Retinal vessel involvement, branch retinal artery occlusion, central retinal artery occlusion (CRAO), and branch retinal vein occlusion were demonstrated in previous reports [4, 610]. Kaushik et al demonstrated branch retinal artery occlusion in a TA patient with left subclavian and common carotid artery occlusion [10].…”
Section: Discussionmentioning
confidence: 99%
“…El compromiso ocular en esta aortitis se debe a isquemia retiniana secundaria al compromiso de grandes arterias, es más raro el compromiso de arterias retinianas; típicamente se ha descrito retinopatía con dilatación de pequeños vasos, microaneurismas capilares y anastomosis (6). También se puede ver cambios retinianos compatibles con retinopatía hipertensiva que se ve en el caso de hipertensión secundario al compromiso de la arteria renal.…”
Section: Dr Héctor Sosa (Medicina Interna)unclassified